2015
DOI: 10.1107/s1600576715013369
|View full text |Cite
|
Sign up to set email alerts
|

Determining the shape and periodicity of nanostructures using small-angle X-ray scattering

Abstract: The semiconductor industry is exploring new metrology techniques capable of meeting the future requirement to characterize three‐dimensional structure where the critical dimensions are less than 10 nm. X‐ray scattering techniques are one candidate owing to the sub‐Å wavelengths which are sensitive to internal changes in electron density. Critical‐dimension small‐angle X‐ray scattering (CDSAXS) has been shown to be capable of determining the average shape of a line grating. Here it is used to study a set of lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 38 publications
0
69
0
1
Order By: Relevance
“…SAXS (Sunday et al, 2015;Sunday et al, 2016) and electron microscopy (Villarrubia et al, 2015) measurements of the described samples are already reported in the literature. We use the line shape reconstructed from SAXS measurements by Sunday et al (Sunday et al, 2015) as a comparison for our GISAXS measurements.…”
Section: Sample Preparationmentioning
confidence: 97%
See 4 more Smart Citations
“…SAXS (Sunday et al, 2015;Sunday et al, 2016) and electron microscopy (Villarrubia et al, 2015) measurements of the described samples are already reported in the literature. We use the line shape reconstructed from SAXS measurements by Sunday et al (Sunday et al, 2015) as a comparison for our GISAXS measurements.…”
Section: Sample Preparationmentioning
confidence: 97%
“…Due to the multi-step production process, the grating lines rest on top of a layer structure consisting of 30 nm of silicon nitride on top of 25 nm of titanium nitride on top of 100 nm of silicon oxide, on the silicon wafer. Further details of the sample production have been published previously (Sunday et al, 2015;Villarrubia M Pflüger, RJ Kline, A Fernández Herrero, M Hammerschmidt, V Soltwisch, M Krumrey: Extracting Dimensional Parameters of Gratings Produced with Self-Aligned Multiple Patterning Using GISAXS et al, 2015). SAXS (Sunday et al, 2015;Sunday et al, 2016) and electron microscopy (Villarrubia et al, 2015) measurements of the described samples are already reported in the literature.…”
Section: Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations